A new elite? Higher education as seen through the lens of young people working in innovative technologies. Issue 3 (3rd July 2021) - Pantea, Maria-Carmen
Abstract : This research explores the significance of higher education among 53 young people from Romania who received prizes in technical competitions, mainly for innovations in robotics and IT. Findings suggest they held strong views on higher education. For some, the conventional roles of university were still, pertinent. However, opting out university or dropping out as a choice were unanticipated findings. This research tentatively suggests that – at least in Romania – higher education in general and technical universities in particular, may fail some young people who are innovative and highly able. The paper communicates to the international literature on university dropout by signaling that the conventional view framed by a sense of failure or social disadvantage, may not always hold. It argues that the social inclusion focus of the 'widening agenda' cannot entirely account for some recent transformations in young people's sense of self and their personal notions of achievement.